2021
DOI: 10.1002/iub.2542
|View full text |Cite
|
Sign up to set email alerts
|

FOXO transcription factors in antioxidant defense

Abstract: Forkhead box, class O (FOXO) family proteins are widely expressed and highly conserved transcriptional regulators that modulate cellular fuel metabolism, stress resistance and cell death. FOXO target genes include genes encoding antioxidant proteins, thus likely contributing to the key role FOXOs play in the cellular response to oxidative stress and supporting the cellular strategies of antioxidant defense, that is, prevention (of the formation of reactive oxygen species), interception (of reactive species pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…S6A). Among the genes for signal transduction pathway, the FoxO family of transcription factors, which regulate the expression of genes in many important physiological events including cell cycle (CC), oxidative stress resistance/DNA repair (OR), immune-regulation (IR), and apoptosis (AP) [ 19 ], was chosen for a more detailed analysis of gene expansion (Additional file 2 : Fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…S6A). Among the genes for signal transduction pathway, the FoxO family of transcription factors, which regulate the expression of genes in many important physiological events including cell cycle (CC), oxidative stress resistance/DNA repair (OR), immune-regulation (IR), and apoptosis (AP) [ 19 ], was chosen for a more detailed analysis of gene expansion (Additional file 2 : Fig. S6B).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, our previous studies in cellular models demonstrated that KRIT1 influenced, directly and dose-dependently, the expression levels of FoxO1, as well as demonstrating that this relationship was strictly correlated with the maintenance of intracellular ROS homeostasis [ 15 ]. Accordingly, FoxO1 is known to be a master transcriptional regulator of cellular responses to ROS and oxidative stress through the induction of genes encoding antioxidant enzymes, including SOD2 and catalase [ 15 , 40 ]. Interestingly, besides its role in antioxidant responses and oxidative stress resistance, it has been established that the FoxO1 transcription factor also plays a key role in insulin signaling and hepatic glucose metabolism [ 34 , 41 , 42 ], suggesting the possible implication of KRIT1 in critical FoxO1-dependent metabolic pathways in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in hepatic glucose metabolism and mitochondrial oxidative phosphorylation are tightly interconnected with changes in redox homeostasis and signaling, and may result in decreased hepatic antioxidant defenses and increased oxidative stress [ 68 , 69 ]. Indeed, whereas the rates of aerobic metabolism and ROS production are positively correlated, the intimate liaison between redox and metabolic pathways is highlighted by their sharing of master regulators, including FoxO1 [ 33 , 40 ]. Therefore, we addressed whether the observed alterations in hepatic glucose metabolism caused by heterozygous loss of KRIT1 in mice were associated with changes in major determinants of hepatic antioxidant defenses, including Nrf2, the master regulator of the antioxidant transcriptional response [ 70 ], and glutathione (GSH), the predominant antioxidant molecule and main regulator of cellular redox status in the liver [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extension of lifespan in fruit fly cohorts by regular consumption of chili-supplemented food can be conferred by the activation of well-known pro-survival pathways. In particular, a number of plant preparations activate the transcription factor FOXO (forkhead box O), increasing the expression of proteins that are necessary to overcome stress conditions [ 1 , 21 ]. Lifespan extension is also achieved by the inhibition of mTOR (mechanistic target of rapamycin) kinase, that activates autophagy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of the effect only in males may imply that the signaling pathway plays an important role for this gender. Genes that encode antioxidant enzymes, including SOD, are targets for the transcription factors FOXO and Nrf2 in mammals [ 21 , 28 , 29 ]. However, much less is known about regulation of antioxidant enzyme expression in fruit flies.…”
Section: Discussionmentioning
confidence: 99%